2021
DOI: 10.1016/j.xkme.2020.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Changes Following Dialysis Initiation and Cardiovascular and Mortality Outcomes in CRIC (Chronic Renal Insufficiency Cohort): A Bioimpedance Analysis Substudy

Abstract: Bioelectrical impedance analysis (BIA) provides a noninvasive assessment of body composition. BIA measures of nutritional (phase angle) and hydration (vector length) status are associated with survival among individuals with chronic kidney disease (CKD), including those receiving maintenance dialysis. However, little is known regarding changes in these parameters with CKD following the high-risk transition to maintenance dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…PhA is directly calculated from the electrical components of resistance (R) and reactance (Xc) and is converted from radians to degrees as the arc tangent of the reactance-to-resistance ratio. A close correlation between nutritional status and PhA has been demonstrated in several studies [ 23 ]; therefore, PhA was used as a marker of nutritional status in our study.…”
Section: Methodsmentioning
confidence: 53%
“…PhA is directly calculated from the electrical components of resistance (R) and reactance (Xc) and is converted from radians to degrees as the arc tangent of the reactance-to-resistance ratio. A close correlation between nutritional status and PhA has been demonstrated in several studies [ 23 ]; therefore, PhA was used as a marker of nutritional status in our study.…”
Section: Methodsmentioning
confidence: 53%
“…Survival analyses significantly showed that age > 72 years PhA ≤ 4° were associated with an increased risk of mortality [ 44 ]. In a multicenter cohort study involving 427 pre-dialysis patients (mean GFR, 7.0 ± 8.7 mL/min/1.73 m 2 ), the PhA decreased by a mean of 0.6 degrees as patients transitioned to dialysis, but this change was not associated with the risk of heart failure, stroke, myocardial infarction, or all-cause mortality [ 45 ]. Thus, more studies are needed to confirm the predictive power of PhA for clinical outcomes when disease stages change in CKD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Survival analyses significantly showed that age>72 years PhA ≤4°were associated with an increased risk of mortality [44]. In a multicenter cohort study involving 427 pre-dialysis patients (mean GFR, 7.0±8.7 mL/minute/1.73 m 2 ), the PhA decreased by a mean of 0.6 degrees as patients transitioned to dialysis, but this change was not associated with the risk of heart failure, stroke, myocardial infarction, or all-cause mortality [45].…”
Section: ) Phase Anglementioning
confidence: 99%